2017
DOI: 10.1093/her/cyx051
|View full text |Cite
|
Sign up to set email alerts
|

Involving mosques in health promotion programmes: a qualitative exploration of the MCLASS intervention on smoking in the home

Abstract: Second-hand smoke (SHS) exposure is high among UK Bangladeshi and Pakistani populations, reflecting higher male smoking prevalence and fewer home smoking restrictions than the general population. The Muslim Communities Learning About Second-hand Smoke (MCLASS) study explored the feasibility and acceptability of implementing SHS education in 14 UK mosques. Religious teachers (RTs) in seven intervention mosques were trained and provided with a culturally appropriate educational package. After the intervention, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 27 publications
1
45
0
Order By: Relevance
“…A second approach that has shown initial promise is currently being trialled in Bangladesh to evaluate the effectiveness of a community-based intervention to reduce SHS exposure at home, primarily targeting men via mosques [48]. This cluster RCT is based on the findings of a pilot trial that concluded that a smoke-free home intervention was acceptable to Muslim communities, and feasible to deliver in mosques [49,50]. If found to be effective in changing smoking behaviour in the home, this approach could be generalizable to other communities with similar male smoking norms where faith-based settings (i.e., churches, mosques, synagogues) play an integral part in their lives [48].…”
Section: Discussionmentioning
confidence: 99%
“…A second approach that has shown initial promise is currently being trialled in Bangladesh to evaluate the effectiveness of a community-based intervention to reduce SHS exposure at home, primarily targeting men via mosques [48]. This cluster RCT is based on the findings of a pilot trial that concluded that a smoke-free home intervention was acceptable to Muslim communities, and feasible to deliver in mosques [49,50]. If found to be effective in changing smoking behaviour in the home, this approach could be generalizable to other communities with similar male smoking norms where faith-based settings (i.e., churches, mosques, synagogues) play an integral part in their lives [48].…”
Section: Discussionmentioning
confidence: 99%
“…Mosques are often places of education for many Muslims, and mosque‐based health education and promotion can be an acceptable and influential means of facilitating positive health behavior change . A mosque‐based intervention to increase exercise levels of South Asian Muslim women in Ontario found an increase in activity levels and self‐efficacy post‐intervention .…”
Section: Discussionmentioning
confidence: 99%
“…Children who are not enrolled in ECD centres can be invited to be part of the MDA program. Faith-based establishments such as churches and mosques are used for healthcare programs in some resource limited settings [57,58] and could be used to mobilize people to enrol their under ve children in the schistosomiasis control MDA program [59,60]. Faith-based establishments could also be used as treatment sites for the MDA program.…”
Section: Structurementioning
confidence: 99%